Pengaruh Kemampuan dan Motivasi Kerja Pegawai terhadap Daya Saing Koperasi pada Unit Salapak di Kota Bandung - Zalsabila, Yunita; Adji, Widwi Handari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cooperative as a form of economic organization that plays an important role in the economy. The purpose of this study was to determine the effect of the ability and work motivation of employees on the competitiveness of cooperatives. The research method used was to collect data through questionnaires which were distributed to cooperative employees involved in operational activities. This study used a quantitative method using the SPSS 23 analysis tool. The total population in the Salapak cooperative unit in the city of Bandung is 15 people. By using the saturated sample technique, the total sample is the entire population, namely 15 people. From the research that has been done, it can be concluded that simultaneously H3 is accepted, meaning that the ability and work motivation simultaneously have a positive effect on competitiveness.